Reciprocal Monogenic Septinomials of Degree 2n3 - Jones Lenny (Annales Mathematicae Silesianae)
We prove a new irreducibility criterion for certain septinomials in ℤ[x], and we use this result to construct infinite families of reciprocal septinomials of degree 2n3 that are monogenic for all n ≥ 1.